2004
DOI: 10.1002/jmri.20227
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of aortic pulse pressure and pressure wave velocity MRI measurement in young adults

Abstract: Purpose:To investigate the feasibility of assessing, noninvasively, aortic pulse pressure (APP) and pulse wave velocity (PWV) in the ascending aorta of young adults by means of velocity-encoded magnetic resonance (MR) imaging. Materials and Methods:In a series of 11 healthy volunteers, velocity-encoded MR imaging provided pairs of magnitude and phase-contrast images. Blood flow velocity and aortic cross-sectional area (CSA) were determined with a 30-msec temporal resolution. A model analysis revealed that vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 16 publications
1
34
1
Order By: Relevance
“…Multivariate analysis showed that both age and CAD were independent risk factors and significantly correlated with the increase in PWV. The results are consistent with data reported in the literature (4,13,23).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Multivariate analysis showed that both age and CAD were independent risk factors and significantly correlated with the increase in PWV. The results are consistent with data reported in the literature (4,13,23).…”
Section: Discussionsupporting
confidence: 93%
“…With the use of phase-contrast magnetic resonance imaging (PC-MRI), PWV can be measured from the slope of the curve of aortic flow plotted against aortic area in systole (12,13), or from the ratio of the traveling distance to the traveling time of the pulse wave (12,14). Although these methods are applicable by noninvasive means, and hence are feasible in the clinical setting, they are subject to inaccuracies owing to assumptions or simplifications made in individual methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By considering the arterial blood volume to be the aortic cross-sectional area multiplied by the slice thickness, and as the slice thickness is constant, the precedent equation becomes (28,29):…”
Section: Discussionmentioning
confidence: 99%
“…To provide a noninvasive estimate of PWV, phase contrast (PC) MRI has been applied in a number of in vivo studies determining blood flow based on flow waveform measurements in single two-dimensional (2D) planes transecting the aorta (8)(9)(10). For PWV estimation, typically transit-time methods are employed estimating temporal differences of specific features of blood flow waveforms, e.g., time from foot to foot or peak to peak, between two locations of the vessel with known distance (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). However, the precision of this method highly depends on the exact calculation of flow difference and distance between only two measuring points (16,25,26).…”
mentioning
confidence: 99%